Prevalensi Larva Anisakis sp. Pada Ikan Tongkol, Ikan Cakalang, Ikan Belanak Dan Ikan Tembang Di Tempat Penjualan Ikan Kecamatan Sulamu, Kabupaten Kupang - Susi Martha Susanti Takubak; Annytha I. R Detha; Diana A Wuri (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Anisakis sp. is an endoparasite in fish that is zoonotic, so it can cause anisakiasis disease in humans when consuming fish with Anisakis sp.. Lof Anisakis sp. predilection for fish digestive tract including intestine, stomach, liver, gonads, eggs and fish muscles. The purpose of this study was to determine the presence of Anisakis sp. and look at the prevalence rate and the degree of infection of Anisakis sp. on mackarel fish, skipjack tuna fish, mullet fish, and sardine fish. The research method was carried out by taking 120 fish samples consisting of 30 mackarel fish, 30 skipjack tuna fish, 30 mullet fish, and 30 sardine fish in fish sale place, Sulamu District, Kupang Regency. The samples were then operated on to observe the presence or absence of Anisakis sp. larvae. in the digestive organs and muscles of fish. Anisakis sp. larvae. which were found were cleaned of debris using 70% NaCl, then fixed with 70% alcohol, and stained with Semichen acetic carmine, then dehydrated in stages using 70%, 85% and 95% alcohol and identification of Anisakis sp. under the microscope. The results of this study found the larvae of Anisakis sp. On mackarel fish, skipjack tuna fish and mullet fish including Anisakis sp. Type I, characterized by the presence of a booring tooth (anterior), venticulus and mucron (posterior). The prevalence of Anisakis sp. larvae. on tuna by 46.66%, skipjack 26.66%, mullet fish 16.66% and tembang fish 0% or no larvae of Anisakis sp. The degree of infection of Anisakis sp. in mackarel fish 19.42 parasites/tail, skipjack tuna fish 17.75 parasites/tail, mullet fish 3 parasites/tail and sardine fish 0 parasites/tail.